SIMPLE FIXED SPACE MAINTAINER BONDED WITH FLOWABLE RESIN COMPOSITE IN PREMATURE LOSS OF MAXILLARY FIRST PRIMARY MOLAR - Heni Primaywati; Margaretha Suharsini (Faculty of Dentistry, Universitas Indonesia, 2006)
The premature loss of primary teeth will make the adjacent tooth drift due to the mesial force of the erupting posterior teeth in the growing child. To overcome this problem a space maintainer is needed. But, space maintainer needs to undergo a laboratorial process, which means needing more time and money. This paper reported a case with premature loss of maxillary first primary molar using space maintainer which can be used immediately, easy to do, and need low cost, a simple fixed space maintainer bonded with flowable resin composite.